Expressão de moléculas da matriz extracelular em células endoteliais resistentes ao anoikis - Lopes, Silvana de Araujo [UNIFESP] (2016)
The extracellular matrix (ECM) is a structure composed of several macromolecules that are differently distributed among tissues of organisms. The interaction between ECM molecules and receptors present on the cell membrane affect several cell properties, including migration, proliferation, differentiation and apoptosis.The process of apoptosis by loss of cell adhesion is named anoikis. This process is considered an important mechanism in preventing independent growth of cell adhesion, because it difficult the binding of cells to inappropriate matrix, thus preventing the colonization of other tissues. However, resistance to anoikis is a critical step in tumor progression and metastasis.Because of the importance and complexity of cell-cell and cell-ECM interactions, studies on the ECM components have important relevance because it represents progress in the development of new drugs for the treatment of cancer.Thus, we studied the expression and localization of various ECM molecules in endothelial cells derived from rabbit aorta (EC), EC transfected with EJ-ras oncogene (EJ-ras EC) and EC resistant to anoikis (Adh1-EC e Adh2-EC).The results show that there was a decrease in the expression of fibronectin, collagen IV and hyaluronic acid as well as an increase in the expression of perlecam, laminin, integrinsαvβ3 and α5β1, MMPs-2 and -9 and hyaluronidases 1, 2 and 3 in anoikis resistant and transfected endothelial cells in relation to parental cells. These results suggest that changes in ECM molecules expression can be directly related to the acquisition of resistance to anoikis in endothelial cells.